Edukasi Kesehatan Gigi Dan Mulut Untuk Meningkatkan Pengetahuan Dan Kesadaran Tentang Pentingnya Kebersihan & Kesehatan Rongga Mulut Pada Masyarakat Wilayah Kerja Puskesmas Ujung Jampea - Risky Sammulia Ananda; Zamli Zamli (Universitas Negeri Gorontalo, 2026)
Oral health problems remain a significant public health concern due to limited knowledge and awareness of proper oral hygiene practices, increasing the risk of dental caries, periodontal disease, and other oral health disorders. This community service program aimed to improve community knowledge, awareness, and skills regarding the importance of maintaining oral hygiene and health in the working area of Ujung Jampea Community Health Center. The program employed health education, tooth-brushing demonstrations, hands-on practice, interactive discussions, and participant skill evaluation through direct observation. A total of 10 participants attended the program. The evaluation results indicated that all participants (100%) successfully understood the educational materials and correctly demonstrated the recommended tooth-brushing technique. In addition to improving knowledge and practical skills, the program enhanced participants' awareness of adopting healthy oral hygiene behaviors and strengthened support for the health center's promotive and preventive programs. Community-based oral health education combined with demonstrations and practical training proved effective in improving oral health literacy and supporting the prevention of oral diseases.